Yavne and Its Secrets : Collected Papers - Haddad, Eli; Nadav-Ziv, Liat; Seligman, Jon (Israel Antiquities Authority, 2022)
The continuing intensive excavations of the surroundings of Tel Yavne conducted by the Israel Antiquities Authority since 2019 have produced evidence of dense settlement from the Chalcolithic period until today, offering the opportunity for multi-disciplinary research on an array of topics. This book is a preliminary study, commencing with an overview of the excavations, and followed by studies concentrating on physical, historical and archaeological aspects.